In silico Screening of Compounds of Piper betle L. leaves for Potential TNF-α Cytokine Inhibition - Thi Hao, Bui; Minh Quan, Tran; Hoang Mai, Tran; Thi Anh Hong, Nguyen; Thi Duong, Trinh; Thuc Thu Huong, Nguyen; Minh Khoi, Nguyen; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Tumor necrosis factor alpha (TNF-α) is a key pro-inflammatory cytokine that plays a central role in immune regulation, inflammatory responses, and host defense against infectious agents. It is closely associated with the pathogenesis of various chronic inflammatory conditions, including rheumatoid arthritis, Crohn's disease, psoriasis, ankylosing spondylitis, and other autoimmune disorders. Piper betle L. is a medicinal plant with potential inhibitory activity against the TNF-α cytokine. In this study, molecular docking was employed to assess the potential of 37 compounds identified in Piper betle L. leaves to bind directly to the TNF-α cytokine protein (PDB ID: 2AZ5) and potentially inhibit its pro-inflammatory activity. The results showed that two compounds, 3-ethyl-3-hydroxy-5α-androstan-17-one and β-sitosterol, exhibited stronger binding affinity to the TNF-α cytokine protein than the positive control, SPD-304. In addition, both compounds also satisfied Lipinski’s rule of five for drug-likeness and demonstrated favorable pharmacokinetic properties and toxicity predictions. Therefore, further research is warranted to explore the potential of these two compounds as TNF-α cytokine inhibitors for the treatment of inflammatory and autoimmune diseases.